PENGEMBANGAN SNACK BAR BERBASIS TEPUNG HANJELI, KACANG ALMOND, FREEZE-DRIED TAPE KETAN HITAM UNTUK DIABETES GESTASIONAL - Novalda Zetridacepa Eka Putri; Fauziyah, Raden Roro Nur; Hapsari, Agustina Indri; Fitria, Mona (Jurusan Gizi Poltekkes Kemenkes Bandung, 2024)
The 2021 International Diabetes Federation report indicated an increase in diabetes cases in Indonesia, placing the country 5th among the top 10 countries or regions with the highest number of diabetes patients, totaling 19.5 million people. The global prevalence of gestational diabetes in 2021 was 14.2%, with Southeast Asia having the second-highest prevalence at 20.8%, following the Middle East and North Africa. Diabetes management is carried out through non-pharmacological therapy, one of which involves managing eating habits. This study aimed to formulate and analyze the quality of snack bars made from hanjeli flour, almonds, and freeze-dried fermented black glutinous rice as an alternative snack for gestational diabetes. The study employed three formulations of hanjeli flour, almonds, and freeze-dried fermented black glutinous rice: F1 (73:13:14), F2 (70:10:20), and F3 (67:15:18), using an experimental research design. An organoleptic test was conducted with 30 panelists using the hedonic method. The results of the organoleptic test showed no significant differences in taste, aroma, color, texture, or overall acceptance (p > 0.05). F3 was identified as the best formula based on the panelists' preferences. Future research is recommended to include high-protein ingredients to enhance the protein content and conduct proximate analysis to improve the accuracy of the nutritional values of the snack bars.